2009
DOI: 10.2478/s11536-009-0010-0
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for breast cancer-related upper extremity lymphedema: Is immediate autologous breast reconstruction one of them?

Abstract: AbstractBreast cancer related upper extremity lymphedema (BCRL) reduces the quality of life of those who have had surgery for breast cancer. The aim of this study is to evaluate the risk factors for BCRL and determine whether immediate autologous tissue breast reconstruction is one of them. A case control study was conducted comparing patients with BCRL (n=97) to surgically treated breast cancer patients without BCRL (control, n=126). The groups were matched for age, type of br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 23 publications
0
12
0
1
Order By: Relevance
“…All eligible individuals were enrolled in the study. In our two previous studies [1,8], lymphedema symptoms and therapy needs in the study control groups were significantly lower than the BRCL patient groups (p < 0.001). Therefore, this study focused on evaluating different occupational characteristics within BCRL patient groups.…”
Section: Methodsmentioning
confidence: 58%
See 2 more Smart Citations
“…All eligible individuals were enrolled in the study. In our two previous studies [1,8], lymphedema symptoms and therapy needs in the study control groups were significantly lower than the BRCL patient groups (p < 0.001). Therefore, this study focused on evaluating different occupational characteristics within BCRL patient groups.…”
Section: Methodsmentioning
confidence: 58%
“…We reported in our previous study that infection of the arm, BMI, and level of hand use are Table 4 Occupation patient groups' symptom related therapy needs significant predictors for BCRL [1]. Another study from our group revealed that occupation, BMI, and postoperative upper extremity infection were risk factors for BCRL but the immediate flap-based breast reconstruction was not [8]. BCRL potential risk factors are grouped into three classes.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Bu sonuç, hastaların lenfödemi, farklı toplumlarda da benzer belirtilerle fark ettiğini göstermektedir. Lenfödem nedenlerini inceleyen çalışmalarda kadınlar; bizim çalışmamızla benzer olarak lenfödem nedenlerini meme kanseri tedavisi, ağır kaldırma, yanlış egzersiz yapma, böcek sokmaları, güneş yanıkları, ve allerjik reaksiyonlar olarak belirtmişlerdir (6, 9) Literatürde, üst kolda enfeksiyonun, ve kolun fazla kullanımının meme kanseri ile ilgili lenfödem gelişimini etkilediği gösterilmiştir (19,20). Yurt dışında yapılan çalışmalardan farklı olarak bu çalışmada, keselenme algılanan lenfödem nedeni olarak belirtilmiştir.…”
Section: Tartışma Ve Sonuçlar Lenfödemi Fark Etmeunclassified
“…It was reported that the occupation of patients which determine the level of hand use is one of the important risk factor for BCRL (Gur et al, 2009). In the current work; we applied the standard occupation classification system 2000 depending on the time of continuous hand usage and the daily total work period.…”
Section: Discussionmentioning
confidence: 99%